2012
DOI: 10.1248/cpb.c12-00447
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Electrokinetic Chromatographic Method for Mianserin Hydrochloride and Analysis of Degradation Products by Mass Spectrometry

Abstract: A simple, stability-indicating micellar electrokinetic chromatography (MEKC) method was developed and validated for the analysis of mianserin hydrochloride in coated tablets. The method employed (hydroxymethyl)aminomethane (TRIS) 50 mM to which sodium dodecyl sulfate (SDS) 50 mM was added at pH 10.6 as the electrolyte and the voltage applied was 25 kV. The capillary used was 48.5 cm long (40.0 cm effective length and 50.0 µm i.d.) and the detection wavelength was 220 nm. Tetracycline was used as internal stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…One of them was identified as N -desmethylmianserin. Structures of two remaining products were not identified (Sfair et al 2012a ). Cytotoxic assay of mianserin irradiated with UV-C was done by Sfair et al by measurement of lactate dehydrogenase releasing into the medium by human mononuclear cells.…”
Section: Photodegradation Studies On Psychotropic Drugsmentioning
confidence: 99%
“…One of them was identified as N -desmethylmianserin. Structures of two remaining products were not identified (Sfair et al 2012a ). Cytotoxic assay of mianserin irradiated with UV-C was done by Sfair et al by measurement of lactate dehydrogenase releasing into the medium by human mononuclear cells.…”
Section: Photodegradation Studies On Psychotropic Drugsmentioning
confidence: 99%
“…S2). Sfair et al (2012b) received a similar spectrum of mianserin in a range m/z 100-300 Da with the fragment ion peaks 222, 208 (most intensive), 161, 146 and 118. On the basis of the spectrum the possible fragmentation for mianserin is shown in Fig.…”
Section: Identification Of Photoproductsmentioning
confidence: 99%
“…It is suspected to be hydroxymianserin or mianserin oxide. According to Sfair et al (2012b) m/z 281 could be identified as oxide formation of members in condensed aromatic ring (hydroxymianserin) or oxidation of nitrogen in the tetracyclic ring (mianserin N-oxide). The presence of fragment ion 253 Da in the spectrum of the compound (Fig.…”
Section: Identification Of Photoproductsmentioning
confidence: 99%
See 1 more Smart Citation